Green Waqf: Sustainable Surplus Perspective Balanced Scorecard Analysis - Moch Mahsun; Ahmad Djalaluddin; Nur Asnawi; Nanik Wahyuni; Nevi Danila; Mohammad Mahbubi Ali (Institut Agama Islam Negeri Madura, 2022)
Green Waqf is a potential method for achieving prosperity, expanding financial inclusion, advancing Islamic justice, and eliminating disparities in poverty levels. This research aims to find a model of good waqf governance to generate sustainable income increases. It will be accomplished by developing an integrated waqf model incorporating an environmental perspective as a balanced scorecard. This study is a literature review that also includes descriptive analysis, and it employs balanced scorecard analysis as its framework for conducting research. The results of the research are used to compile the data. During this phase of the process, data collection methods are utilized in order to locate and collect information pertinent to green Waqf, waqf productivity, the balanced scorecard, and an Islamic perspective in a structured manner. The conversation illuminated that the Waqf regulatory system was not functioning at its full potential and required enhancement. The conversation inspired that the Waqf regulatory system needed to be operating at its full potential; this needs to be emphasized, especially as a response to the low levels of waqf literacy, nazhir capacity, and technology utilization. The waqf management system does not exist in a vacuum free of defects. It is hoped that by using a balanced scorecard, gaps will be closed by implementing strategies, particularly the productivity and growth strategies, to maximize waqf management and provide an understanding of waqf ecosystems, thereby increasing the productivity of waqf management, generating the profitability of waqf assets, and maximizing the distribution of Waqf to beneficiaries (mauquf 'alaih). It will result in closing the gaps.